Outcome of the risk‐stratified desensitization protocol in donor‐specific antibody‐positive living kidney transplant recipients: a retrospective study. (11th May 2018) - Okada, Daigo; Okumi, Masayoshi; Kakuta, Yoichi; Unagami, Kohei; Iizuka, Junpei; Takagi, Toshio; Ishida, Hideki; Tanabe, Kazunari
Summary: Acceptable outcomes of donor‐specific antibody (DSA)‐positive living kidney transplantation (LKT) have recently been reported. However, LKT in crossmatch (XM)‐positive patients remains at high‐risk and requires an optimal desensitization protocol. We report our intermediate‐term outcomes of XM‐positive LKT vs. XM‐negative LKT in patients who underwent LKT between January 2012 and June 2015 in our institution. The rate of acute antibody‐mediated rejection (ABMR) within 90 days postoperation, graft function, and patient, and graft survival rates at 4 years were investigated. Patients were divided into three groups: XM−DSA− ( n = 229), XM−DSA+ ( n = 36), and XM + DSA+ ( n = 15). The XM + DSA+ group patients underwent desensitization with high‐dose intravenous immunoglobulin, plasmapheresis, and rituximab. The rates of ABMR within 90 days in the XM−DSA−, XM−DSA+, and XM + DSA+ groups were 1.3%, 9.4%, and 60.0%, respectively ( P < 0.001). There were no significant differences in the graft function throughout the observational period, the 4‐year patient or graft survival rates among three groups. This study showed that intermediate‐term outcomes of XM‐positive LKT were comparable to XM‐negative LKT. However, our current desensitization protocol cannot avert ABMR within 90 days, and XM positivity is still a significant risk factor for ABMR. Further refinement of the current desensitization regimen is required.